Inability to capture with increasing current strength: Is this near‐field or far‐field? - Liu, Fang‐Zhou; Liao, Hong‐Tao; Zhan, Xian‐Zhang; Shehata, Michael; Ehdaie, Ashkan; Chen, Qiu‐Fan; Wu, Shu‐Lin; Xue, Yu‐Mei; Wang, Xun‐Zhang (Journal of cardiovascular electrophysiology, 2020)
We present a case of wide‐complex tachycardia in which the clinical electrophysiological diagnosis was considered to be bundle branch re‐entry ventricular tachycardia. A series of ventricular entrainment attempts were performed from the left and right ventricular septum to confirm the diagnosis. Entrainment pacing with a general current output (10 mA) was performed from the right ventricular septum with manifest fusion and a post‐pacing interval similar to tachycardia cycle length. Thereafter, another entrainment attempt with a greater current output (20 mA) was performed from the same site. Paradoxically, concealed fusion was demonstrated by selective RB capture only, though there was no clear “RB” potential seen. In this case, we attempt to explain and illustrate the mechanism of paradoxical near‐field inability to capture with increasing current strength.